2022
DOI: 10.1210/clinem/dgac509
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss, Lifestyle Intervention, and Metformin Affect Longitudinal Relationship of Insulin Secretion and Sensitivity

Abstract: Context Insulin secretion and sensitivity regulate glycemia, with inadequately compensated deficiencies leading to diabetes. Objective We investigated effects of weight loss, an intensive lifestyle intervention (ILS), and metformin on the relationship between insulin secretion and sensitivity using repository data from 2931 participants in the Diabetes Prevention Program clinical trial in adults at high risk of developing typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…This is consistent with previous results that indicated that in people with increased diabetes risk (in this case carriers), the most important factor for delaying or preventing diabetes is the ability to reach glucose homeostasis by adequately compensating for decreased insulin sensitivity (insulin secretion compensation). 20 The variant associated significantly with the prevalence of retinopathy, but not with the other complications. R1420H carriers had a higher prevalence (but not significantly) of retinopathy even in observations without diabetes; signs of diabetic retinopathy have been previously found in people without diabetes in this population.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This is consistent with previous results that indicated that in people with increased diabetes risk (in this case carriers), the most important factor for delaying or preventing diabetes is the ability to reach glucose homeostasis by adequately compensating for decreased insulin sensitivity (insulin secretion compensation). 20 The variant associated significantly with the prevalence of retinopathy, but not with the other complications. R1420H carriers had a higher prevalence (but not significantly) of retinopathy even in observations without diabetes; signs of diabetic retinopathy have been previously found in people without diabetes in this population.…”
Section: Discussionmentioning
confidence: 87%
“…This is consistent with previous results that indicated that in people with increased diabetes risk (in this case carriers), the most important factor for delaying or preventing diabetes is the ability to reach glucose homeostasis by adequately compensating for decreased insulin sensitivity (insulin secretion compensation). 20 …”
Section: Discussionmentioning
confidence: 99%
“…In this work, we found elevated levels of arachidonic acid and its precursor, linoleic acid, in T2D subjects treated with diet and lifestyle modifications as compared to ND controls, with metformin therapy reversing these changes. While we did not directly measure β-cell function in our study, others have found metformin augments insulin secretion, even in the context of reduced insulin demand (Vazquez Arreola et al, 2022). Therefore, it is possible decreased β-cell PGE2 is at least partially responsible for metformin's effects.…”
Section: Improved Pancreatic β-Cell Function May Occur With Metformin...mentioning
confidence: 80%
“…Metformin is one of the most commonly used oral antidiabetic agents in treating type 2 diabetes, and it can also be used in prediabetic individuals to retard diabetes progression. Some studies demonstrate that metformin positively affects weight loss due to its mechanism, and some demonstrate a neutral effect 6 . In overweight and obese diabetic patients, 5–10% weight loss improves glycemic control and reduces the need for antidiabetic drugs 7 ., although providing weight loss is problematic in diabetic patients due to polypharmacy, weight gain side effects of drugs, and glycemic fluctuations 8 .…”
Section: Introductionmentioning
confidence: 99%